A cohort study of anatomical landmark-guided midline versus pre-procedure ultrasound-guided midline technique of spinal anesthesia in elderly patients undergoing orthopedic surgery - Harsha Hemraj Narkhede; Deepa Kane; Viral Parekh; Indrani Hemantkumar (Journal of Anaesthesiology Clinical Pharmacology, 2019)
Background and Aims: The primary objective of the study was to compare the number of attempts and number of passes of spinal needle insertion and secondary objective was to compare complications, bloody tap, and patient discomfort in anatomical landmark-guided versus pre-procedure USG-guided midline technique of spinal anesthesia in elderly patients posted for orthopedic surgery. Material and Methods: In this a prospective observational cohort study, 60 patients of either sex, ASA grades I–III, and aged more than 65 years were randomly allocated to 2 groups of 30 patients each. In group AG (Anatomical landmark guided), standard landmark technique was used. In group UG (Ultrasound guided), pre-procedure ultrasound guided marking for insertion point of a spinal needle was done before giving spinal anesthesia. Patients in both the groups were compared on the basis of number of attempts, number of passes, vascular injury (bloody tap), pain score, complications, and procedure time. Results: Successful dural puncture on the first needle insertion attempt was achieved more in UG group (90%) than in AG group (50%) (P < 0.05). Dural puncture was not achieved in only 3.3% patients in the UG group even after three midline attempts at spinal needle insertion. Mean of the number of passes was more in AG group (1.90) than in UG group (1.07) (P < 0.05). VAS (Visual Analogue Scale) score was 0.4 in AG group and 0.3 in UG group (P > 0.05). Group UG had shorter procedure time (2.25 min) than AG group (4.35 min). Conclusion: Preprocedure ultrasound imaging is a very useful tool to facilitate the performance of central neuraxial blockade in patients with difficult anatomical landmarks, especially in elderly patients.